Highly Efficient Autologous HIV-1 Isolation by Coculturing Macrophage With Enriched CD4+ T Cells From HIV-1 Patients - Xufré, Cristina; González, Tanía; Leal, Lorna; Trubey, Charles M.; Lifson, Jeffrey D.; Gatell, José María; Alcamí, José; Climent, Núria; García, Felipe; Sánchez-Palomino, Sonsoles (Frontiers in Virology, 2022)
We describe a novel HIV autologous isolation method based in coculturing macrophages and CD4+ T cell enriched fractions from peripheral blood collected from antiretroviral treated (ART) HIV patients. This method allows the isolation of high viral titres of autologous viruses, over 1010 HIV RNA copies/mL, and reduces the time required to produce necessary amounts for virus for use as antigens presented by monocyte-derived myeloid cells in HIV therapeutic vaccines approaches. By applying these high titre and autologous virus produced in the patient-derived cells, we intend to elicit a boost of the immunological system response in HIV therapeutic vaccines in clinical trials.